2020
DOI: 10.1016/j.bja.2020.05.066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signatures of perioperative myocardial injury after elective noncardiac surgery: a prospective observational mechanistic cohort study

Abstract: Background: Elevated plasma or serum troponin, indicating perioperative myocardial injury (PMI), is common after noncardiac surgery. However, underlying mechanisms remain unclear. Acute coronary syndrome (ACS) is associated with the early appearance of circulating microRNAs, which regulate post-translational gene expression. We hypothesised that if PMI and ACS share pathophysiological mechanisms, common microRNA signatures should be evident. Methods: We performed a nested case control study of samples obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…The network suggested that hsa-mir-1-3p might regulate gene expression in IPAH. Previous studies have shown elevated hsa-mir-1-3p in perioperative myocardial injury patients ( May et al, 2020 ). Further research is needed to verify the mechanism linking hsa-mir-1-3p to IPAH.…”
Section: Discussionmentioning
confidence: 95%
“…The network suggested that hsa-mir-1-3p might regulate gene expression in IPAH. Previous studies have shown elevated hsa-mir-1-3p in perioperative myocardial injury patients ( May et al, 2020 ). Further research is needed to verify the mechanism linking hsa-mir-1-3p to IPAH.…”
Section: Discussionmentioning
confidence: 95%
“…For the control PBS-treated mouse group, the number of miRs classed by tags per million (TPM) interval were 438 miRs where TPM interval 0–3.57; the 139 miRs where TPM interval 3.57–15; the 117 miRs where TPM interval 15–60 and the 192 microRNAs where TPM > 60. In a recent study, human blood EVs and NGS study with the same analysis platform of ours, revealed 345 unique microRNA where TPM ≥ 1 and 164 unique microRNAs where TPM ≥ 10 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent investigations using blood samples from the VISION 32 and METS 25 cohorts suggest myocardial injury has an inflammatory etiology. 41,42 Based on these facts, it is unlikely that all patients classified as having MINS had myocardial ischemia, and in my opinion, as an endpoint or a diagnosis, MINS is fundamentally flawed.…”
Section: Asymptomatic Pulmonary Embolism Is Common and Ismentioning
confidence: 99%
“…40 Des recherches récentes utilisant des échantillons de sang des cohortes des études VISION 32 et METS 25 suggèrent que la lésion myocardique aurait une étiologie inflammatoire. 41,42 Base´sur ces faits, il est peu probable que tous les patients classifie´s comme ayant une MINS souffraient d'une ische´mie myocardique, et a`mon avis, que ce soit comme crite`re d'e´valuation ou comme diagnostic, la MINS est fondamentalement errone´e.…”
Section: Valeur Pronostique Des Lésions Myocardiques Postopératoiresunclassified